Zapažanja o Prijedlogu Zakona o provođenju odluka sudova / Obeservations on the Proposal of the Law on Implementation of Decisions of Courts: Federacija Bosne i Hercegovine na pogrešnom i neustavnom putu? / Federation of Bosnia and Herzegovina on the Wrong and Unconstitutional Path? - Išerić, Harun (Pregled: časopis za društvena pitanja / Periodical for social issues, 2022)
The text critically analyses the provisions of the Proposal of the Law on Implementation of the Decisions of Courts in the Federation of BiH concerning their compliance with the Constitution of BiH, precision, Article III/3 /b and the Decision on the Representative/Agent of the Council of Ministers of Bosnia and Herzegovina before the European Court of Human Rights and the Office of the Representative/Agent of the Council of Ministers of Bosnia and Herzegovina before the European Court of Human Rights, as well as the expediency of passing such a law.